Restless Legs Syndrome in a Community Sample of Korean Adults: Prevalence, Impact on Quality of Life, and Association with DSM-IV Psychiatric Disorders - CHO, Seong-Jin; JIN PYO HONG; HAHM, Bong-Jin; HONG JIN JEON; SUNG MAN CHANG; MAENG JE CHO; LEE, Hochang B (Sleep (New York, N.Y.), 2009)
Conflicting reports on prevalence of RLS exist in Asian countries due to differences in sampling strategies and assessment instruments. We assessed the prevalence, correlates, quality of life, and psychiatric comorbidity of RLS in South Korea. Cross-sectional nationwide survey. Nationally representative sample of 6,509 Korean adults aged 18-64. Face-to-face interviews based on the Korean translation of the four features of RLS defined by the International RLS Study Group (IRLSSG), the Korean version of Composite International Diagnostic Interview (K-CIDI), and EuroQol (EQ-5D) were conducted for all participants. The weighted prevalence of RLS in South Korea was 0.9% (men, 0.6%; women, 1.3%). Subjects with RLS had a lower quality of life according to EQ-5D than those without RLS. Adjusted odds ratio for lifetime diagnosis of DSM-IV major depressive disorder (2.57, 95% confidence interval [1.33, 4.96]), panic disorder (18.9 [4.72, 75.9]) and posttraumatic stress disorder (3.76 [1.32, 10.7]) suggest strong association between RLS and DSM-IV depression and anxiety disorders. Prevalence of RLS estimated based on the IRLSSG diagnostic criteria is substantially lower in South Korea than in Western countries. Differences in culture and risk factors that affect the expression of RLS may vary across the countries.